TRANSFORMASI PENGAMBILAN KEPUTUSAN BERBASIS DATA: PERAN STRATEGIS PERANGKAT LUNAK DALAM SISTEM INFORMASI MANAJEMEN PENDIDIKAN ISLAM - Agustina, Muvtia; Saipul Annur; Ade Rosad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Software is a core component of Management Information Systems (MIS) that transforms data into accurate, relevant, and timely information to support managerial decision-making. In the context of Islamic education management, software functions not merely as an administrative tool but as a strategic instrument to promote transparent, accountable, and data-driven governance. This paper aims to analyze the role of software in optimizing managerial decision effectiveness, identify technical and non-technical challenges in MIS integration, and examine the impact of adopting emerging technologies such as artificial intelligence (AI), cloud computing, and low-code platforms. The findings indicate that MIS software enhances decision quality through real-time information, analytical features, and cross-unit integration. However, its implementation faces challenges including legacy system compatibility, data security and privacy concerns, infrastructure limitations, user resistance, and human resource readiness. Examples of educational MIS software in Indonesia include Dapodik, EMIS, Siakad, SIMPATIKA, and Moodle, which support data management and quality improvement in education. Properly managed, MIS software becomes a fundamental pillar in the digital transformation of Islamic educational institutions.